Association between first attempt buffalo concussion treadmill test and days to recovery in 855 children with sport-related concussion: A historical cohort study and prognostic factors analysis - Lalji, R.; Hincapié, C. A.; Macpherson, A.; Howitt, S.; Marshall, C.; Tamim, H. (Clinical Journal of Sport Medicine, 2023)
Objective: Little is known about the prognostic value of the Buffalo Concussion Treadmill Test (BCTT) after the acute phase of sport-related concussion (SRC). We examined the added prognostic value of the BCTT performed 10 to 21 days after SRC in children, in addition to participant, injury, and clinical process characteristics on days to recovery.